Production and Preparation of Blast-furnace Flux - P. C. Hodges (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1936)
WHILE there is very little romance connected with the operation of a stone quarry, yet to those who have participated in the growth and development of a business that has been a pioneer in its field and that FIG. 1.-LOCATION OF PROPERTY OF MARBLE CLIFF QUARRIES COMPANY. has been in continual operation two-thirds of a century there is bound to be a background of experience, which if properly capitalized, brings progress as well as satisfaction in its accomplishment.